2020
DOI: 10.5010/jpb.2020.47.2.124
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of sweet potato accessions using ARMS-PCR based on SNPs

Abstract: The sweet potato (Ipomoea batatas [L.] Lam.) is the sixth-most important crop in the world following rice, wheat, potato, maize, and cassava. Four varieties ('Beniharuka', 'Annobeni', 'Pungwonmi', 'Hogammi') and their Japanese cultivars are broadly distributed in South Korea. In the Korean marketplace, sweet potatoes are classified by color and shape, not by variety, making it necessary to differentiate varieties for uniform production and consumption. In this study, molecular markers were developed to disting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…As third-generation molecular markers, SNPs are highly stable and widely used for studies of crop molecular genetics (Brookes, 1999; Yu et al ., 2020). Tetra-primer ARMS PCR is a derivative technique based on standard PCR that can be specifically used to detect SNPs (Yang et al ., 2018), which is economical, rapid, simple and has been successfully applied for analysis and identification of genotypes in rice, wheat, sweet potato and other crops (Hou et al ., 2013; Zhang et al ., 2015; Park et al ., 2020). Yang et al .…”
Section: Discussionmentioning
confidence: 99%
“…As third-generation molecular markers, SNPs are highly stable and widely used for studies of crop molecular genetics (Brookes, 1999; Yu et al ., 2020). Tetra-primer ARMS PCR is a derivative technique based on standard PCR that can be specifically used to detect SNPs (Yang et al ., 2018), which is economical, rapid, simple and has been successfully applied for analysis and identification of genotypes in rice, wheat, sweet potato and other crops (Hou et al ., 2013; Zhang et al ., 2015; Park et al ., 2020). Yang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these methods do not need fully expanded leaves but can be applied in any growth stage using any plant tissues (such as seeds, fruits, and young leaves), making plant growth redundant 51 . With these advantages, molecular marker-based methods are being used in many breeding institutes and companies for routine identification in a wide range of ornamental, vegetable, fruit, and cereal crops 52 57 . However, their disadvantages are also apparent.…”
Section: Discussionmentioning
confidence: 99%
“…The inner forward or outer reverse and outer forward or inner reverse primer combination yield allele-specific amplicons depending on the genotype of the sample used. The placing of the inner primers is not the same as those of the corresponding outer primer to produce amplicons with different sizes and easily visualized on gel and distinction is made accordingly [42][43][44].…”
Section: Tetra Arms Allele Specific Pcrmentioning
confidence: 99%
“…SNP markers identified by genotyping-by-sequencing were used to distinguish four varieties of sweet potato through tetra-primer ARMS-PCR method. It was shown that three variety-specific fragments (164 bp and 241 bp of SNP 04-27457768 and 292 bp of SNP 03-16195623) were amplified in the Single Nucleotide Polymorphisms: A Modern Tool to Screen Plants for Desirable Traits DOI: http://dx.doi.org/10.5772/intechopen.94935 'Beniharuka', 'Pungwonmi', and 'Annobeni' sweet potato varieties [43]. Some SNP markers developed by Angiolillo et al [46] was used to resolve the issue of nomenclature for 65 olive samples as the markers were able to discriminate 77% of the olive cultivars.…”
Section: Tetra Arms Allele Specific Pcrmentioning
confidence: 99%